1963
DOI: 10.1071/bi9630818
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Fine Structure of the Wax Layer of Sultana Grapes

Abstract: The surface waxy bloom of sultana grapes has been studied using the carbon. replica technique in combination with electron microscopy. This layer consists of a series of overlapping wax platelets, each of which is about 0·1 f' wide. The air spaces between the wax platelets become filled with liquid when sultana berries are dipped in commercial emulsions known to accelerate their drying rate. Washing in distilled water removes this layer of dipping emulsion from the surface. The appearance of dipped and washed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

1970
1970
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 5 publications
1
30
1
Order By: Relevance
“…(Pi-Pa)At 0.025 g H20 fruit-' h-' RDT r 3.600sh-' (98 -70)RH 17 Therefore, r = 106 s cm-' or rounded to two significant figures = IlO0s cm-'. account for the residual gas exchange capacity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Pi-Pa)At 0.025 g H20 fruit-' h-' RDT r 3.600sh-' (98 -70)RH 17 Therefore, r = 106 s cm-' or rounded to two significant figures = IlO0s cm-'. account for the residual gas exchange capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Opinions differ widely concerning the relative contributions of the various mechanisms proposed to account for gas exchange in harvested fruits, although usually it is tacitly assumed that water and gases move by the same pathway. (17). Alternatively, it has been suggested that CO2 moves through the skin and 02 through the lenticels of fruits (23), and more recently Burg and Kosson (14) proposed that water moves preferentially through a liquid water phase, whereas gases move through airfilled pores.…”
mentioning
confidence: 99%
“…Since this type of surface structure is a strong barrier to the transpiration from berries, the chemical nature and fine structure of the wax have been investigated by many workers in `Thompson Seedless (Sultana)' , the most extensively grown raisin grape in the world (1,2,5,6,7,8,9,10,11). On the table grape cultivars, however, there have been hardly any detailed reports on them.…”
Section: Introductionmentioning
confidence: 99%
“…According ta their results, dipping does not remove the waxy material but only modifies the surface probably from hydrophobie ta hydrophillic, thus enabling wetting. Chambers and Possingham (1963) studied the surface waxy bloom of Sultana grapes using the carbon replica technique in combination with e1ectron microscopy. According ta their observations this layer consists ofa series oftiny wax plate1ets ofabout 0.1 J.lIIl wide.…”
Section: Hot Air Dryingmentioning
confidence: 99%